Reversible Posterior Encephalopathy Syndrome Secondary to Sunitinib - Costa, Ricardo (Hindawi Publishing Corporation, 2014)
Reversible posterior leukoencephalopathy syndrome (RPLS) is clinical radiologic condition associated with neurological symptoms and cerebral white matter edema. It has been associated with uncontrolled hypertension, eclampsia, immunosuppressants, and more recently the use of antiangiogenic drugs. Sunitinib is an inhibitor of the vascular endothelial growth factor receptor widely used in the treatment of metastatic renal cell carcinoma (RCC). We report a rare case of RPLS occurring on therapy with sunitinib in a patient with RCC. Our aim is to highlight the importance of considering RPLS as a diagnostic possibility and to hold sunitinib for RCC patients presenting with neurologic symptoms.